Des trois connaissances théologiques aux trois sagesses selon Hugues de Balma, Guigues du Pont et Denys le Chartreux Étapes d’une épistémologie cartusienne de la théologie - Trottmann, Christian (Mystik unterwegs. Theologia mystica und revelationes in kartäusischen Händen, 2022)
Ook verschenen als Studia Cartusiana 7

Les manuscrits de la bibliothèque de la chartreuse d’Utrecht au XVe siècle. Mystique, affect et images - Falque, Ingrid (Mystik unterwegs. Theologia mystica und revelationes in kartäusischen Händen, 2022)

Ruusbroec through the looking glass. Henry of Coesfeld’s devotional theology and its influence on Nicholas of Cusa - Gaens, Tom (Mystik unterwegs. Theologia mystica und revelationes in kartäusischen Händen, 2022)
Ook verschenen als Studia Cartusiana 7

Between Norms and Books. Constructing Authority in the Fifteenth Century - Signori, Giacomo; Dlabačová, Anna; Abram, Marieke (Shaping Authority. How Did a Person Become an Authority in Antiquity, the Middle Ages and the Renaissance?, 2016)